2020
DOI: 10.1177/1741143220962105
|View full text |Cite
|
Sign up to set email alerts
|

Pedagogical leadership and children’s well-being in Finnish early education

Abstract: In this paper, we present research that focuses on pedagogical leadership that is evaluated by the staff in the early education unit. The evaluations relate to the observed indicators of the well-being of children and leadership evaluations conducted by the early education centre directors. The methods include systematic observation of children, educators’ evaluation of leadership and directors’ evaluation of their leadership. The measurements are independent of each other. The data were collected between 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…While early childhood education did not emerge on this term map, we noted that it was present on maps that used a somewhat lower threshold (e.g. Fonsén et al, 2020;Gibbs, 2020).…”
Section: Past and Present Topical Foci Of Emalmentioning
confidence: 80%
“…While early childhood education did not emerge on this term map, we noted that it was present on maps that used a somewhat lower threshold (e.g. Fonsén et al, 2020;Gibbs, 2020).…”
Section: Past and Present Topical Foci Of Emalmentioning
confidence: 80%
“…As PL is theoretically, conceptual, and empirically explored, more and more scholars are trying to understand its dimensions, applications, and effects on teaching and learning. From content analysis, it can be highlighted that most articles defined pedagogical leadership as an approach that involves a collaborative process of planning (Yang & Lim, 2020;Zohar & Cohen, 2016), decision making (Ho, 2010), action (Male & Palaiologou, 2017;Seiser, 2020) and evaluation (Fonsen et al, 2020(Fonsen et al, , 2020 in which teachers and administrators define shared goals for their school (Garcia-Martinez & Martin-Romera, 2019;Muli et al, 2017). Pedagogical leaders consult with interested parties (Gonzalez-Fernandez et al, 2020) about the means to reach those goals, and create an environment in which all students will have greater access to highquality educational opportunities (Reis & Flores, 2014;Rogers & Grunewald Nichele, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It can be said that the study of PL is elusive and emerging in the body of knowledge. In addition, many international findings are also centralized on the importance (Muli et al, 2017;Rogers, 2019), effectiveness (Angelo & McCarthy, 2020;Fonsen et al, 2020), and evaluations of observed practices from PL (Culhane et al, 2018). Because PL tends to overlap with Instructional Leadership, Distributed leadership, and Situational leadership (Male & Palaiologou, 2015), there is no prominent instrument to measure Pedagogical leadership in this region yet.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of music in the groups was measured with Reunamo's evaluation model (Fonsen et al 2020;Rintakorpi and Reunamo 2017). The emphasis of music was evaluated with the statement, 'Music and song are important in our everyday education' on a scale of one (does not describe) to five (describes very well).…”
Section: Learning Environment Evaluationsmentioning
confidence: 99%